BEST PRACTICE EDUPRENEURSHIP BERBASIS PEMBELAJARAN SENTRA BERKEBUN DI PAUD DARUSSALAM BOJONEGORO - Sriyanti Sriyanti; Aulia Singa Zanki (Universitas Al-Hikmah Indonesia, 2021)
This qualitative research uses a case study approach. The data source was obtained by interviewing three gardening center teachers. This study aims to explain three things. (1) learning edupreneurship with gardening centers in PAUD Darussalam, (2) obstacles faced, (3) efforts to overcome these obstacles. The results obtained are as follows: first, edupreneurship learning in PAUD Darussalam was carried out by utilizing hydroponic plants in a green house. Second, the obstacles faced in learning edupreneurship in gardening centers: (1) the location on the roof of the building is hot, (2) there is no special nursery for each class, (3) the children cannot observe the development of plants step by step, ( 4) pests that attack plants, (5) access to narrow locations, (6) post-harvest sales and marketing processes that do not yet exist, (7) there are students who do not participate in activities properly, (8) there is no clear SOP for learning about gardening centers . Third, efforts are made to overcome obstacles during gardening center learning: (1) regulating learning hours so that children do not overheat, (2) providing learning support facilities for gardening centers, (3) clear class and hour division, (4) lifting green house management officers, (5) appoint special officers to assist teachers, (6) carry out marketing and collaborate with traders, (7) design activities in gardening centers to make them more attractive, (8) compile SOPs for learning gardening centers